Redox status on different regions of the central nervous system of obese and lean rats treated with green tea extract - Macedo, Rita Cassia; Bondan, Eduardo Fernandes [UNESP]; Otton, Rosemari (Taylor & Francis Ltd, 2019)
Objectives: The purpose of this study was to evaluate some indicators of redox status, and inflammation on different regions of the central nervous system (CNS) of obese rats treated with green tea (GT). We hypothesized that obesity could affect the redox balance in different brain regions due to the diverse nature of the cells as well as the selective neuronal vulnerability to oxidative stress, and GT could triggers benefits effects restoring the redox status. Methods: Male Wistar rats were treated with GT by gavage (12 weeks/5 days/week; 500 mg/kg of body weight) and obesity was induced by cafeteria diet (8 weeks). After this period, the animals were killed and brain tissue (cerebral cortex, cerebellum, and brainstem) was removed to evaluate oxidative stress and inflammation (cytokine release). Results: We showed that the cafeteria diet had little effect on redox balance in the cerebral cortex and cerebellum; however, the brainstem was the region of the CNS most sensitive to cafeteria diet-induced redox unbalance. GFAP expression was increased in the cerebral cortex of obese rats and reduced by GT. It was also evident that GT treatment had numerous beneficial effects against oxidative damage to biomolecules in all brain regions analyzed. Discussion: Our study established that different CNS regions show selective neuronal vulnerability when exposed to a diet enriched with fats and sugars, and the beneficial effect of GT was similar among these regions. We conclude that GT could be a good strategy for improving and maintaining brain function under healthy and pathological conditions.
Keywords: Obesity; polyphenols; cerebral cortex; oxidative stress; inflammation